Pengelolaan Konflik Sumber Daya Alam Terbarukan di Perbatasan dalam Pendekatan Ekologi Politik - Herdis Herdiansyah (Jurnal Hubungan Internasional, 2019)
The different interest among actors (government, society, and corporations) has become one of the causes of conflict in natural resources managements. In border areas, conflict arises because of abundant land availability and diverse natural resources that have a potency to be utilized for a variety of purposes.Meanwhile, the political ecology approach sees these differences of interest arise from economic, social, and political motives or it can be driven by an environmental control. Political ecology approach can help to illustrate the phenomenon, by linking the environmental condition to the process of the political economy. Political ecology becomes operational when it acts as an environmental policy and spur the government to act collaboratively with privates and communities. In addition, natural resources management must include the right and responsibilities in the future. To assuring the conflict of natural resources management at the border will not escalate, the approach of the security law need to be implemented at the border besides the welfare approach.